2019
DOI: 10.1093/emph/eoz025
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evolution of gallium resistance in Escherichia coli

Abstract: Background and Objectives Metallic antimicrobial materials are of growing interest due to their potential to control pathogenic and multidrug-resistant bacteria. Yet we do not know if utilizing these materials can lead to genetic adaptations that produce even more dangerous bacterial varieties. Methodology Here we utilize experimental evolution to produce strains of Escherichia coli K-12 MG1655 resistant to, the iron analog, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 47 publications
0
27
2
Order By: Relevance
“…However, in prior studies we have deployed more direct methods to test whether the genomic variants we discovered should and actually do confer resistance. For example, we have utilized computational modeling of 3-dimensional structures of altered proteins to test their affinity for ionic metals [ 12 , 15 , 42 ]. These studies showed the alteration in the protein caused by the variant resulting from the selective sweep did reduce or increase the affinity to the target metal compared to the controls/ancestor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in prior studies we have deployed more direct methods to test whether the genomic variants we discovered should and actually do confer resistance. For example, we have utilized computational modeling of 3-dimensional structures of altered proteins to test their affinity for ionic metals [ 12 , 15 , 42 ]. These studies showed the alteration in the protein caused by the variant resulting from the selective sweep did reduce or increase the affinity to the target metal compared to the controls/ancestor.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli MG1655 (ATCC #47076) was used in this study because it does not have plasmids and its circular chromosome is composed of 4,641,652 nucleotides (GenBank: GenBank: 117 NC_000913.3; Riley et al 2006). All of our previous studies of ionic and nanoparticle resistance have used this strain [ 13 , 14 , 15 ]. This strain is the ancestor of all the selection treatments (FeNP and Controls) evaluated in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Both G210C and A526T were also detected in our 45-day iron (II) adapted populations [ 27 ]. In red are two mutations (N169K and G400S) which were detected in gallium (iron analog) resistant strains [ 38 ] and as shown, map to similar regions as the iron resistant mutations. ( B ) The iron-citrate complexed structure (PDB1PO3) was also used to map two of the three iron resistant residues (D87Y lies in an unstructured region and therefore could not be mapped) and the gallium mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Second, gallium is an iron analog. In our previous work, this strain of E. coli also acquires mutations in fecA as a result of gallium resistance which could account for the increased optical densities in the adapted strain in the metal [ 38 ]. What is most concerning is the multi-drug resistance acquired in this strain, which indicates that these strains have the potential to be even more harmful than originally anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive evolution strategy can be used to obtain strains with an evident product tolerance, [ 81 ] substrate utilization, and cell survival phenotype after evolution. [ 40,82 ] The goal of adaptive evolution is to obtain transporter mutants with higher transport efficiency, substrate specificity, or conversely, mutants with better substrate compatibility. For instance, an adaptive evolution was conducted using the hexose transporter CiGXS1 FIM in yeasts, and glucose–xylose cotransport mutants were selected based on their survival on xylose and glucose plates.…”
Section: Transporter Engineering In Microbial Cellsmentioning
confidence: 99%